PENGARUH HARGA DAN FASILITAS TERHADAP KEPUTUSAN MENGINAP DI ALOFT HOTEL JAKARTA WAHID HASYIM - Sofiani Sofiani (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2023)
Aloft Hotel Jakarta Wahid Hasyim is. wrong. one. hotel. star. 4 located in downtown Jakarta. Located in a location. strategic. make. Many people. choose. for. stay overnight. in the area. This great opportunity was also seen by other parties so that many hotels were established in the area. Study. this. done. to find out the effect. price. and. decision facility. stay overnight. at Aloft Hotel Jakarta Wahid Hasyim. Method. research that. used. on research. this. is. quantitative method with a total sample of 130 respondents. Technique. collection. data. on. study. This is done by distributing questionnaires and observations. The test method in research uses test. validity and reliability, test. normality, multicollinearity and heteroscedasticity tests, T tests, F tests, multiple linear regression tests and tests of the coefficient of determination and mean tests. The results of the tests carried out show that the effect. price and facilities to the decision. stayed at Aloft Hotel Jakarta Wahid Hasyim by 67.3%. The influence given is included in the strong category. From the results of partial testing (T test) on the variable price of 5.573 and facilities of 7.381. Test result. in a manner. simultaneous (F test) on both variables of 133.745, where the variables have a significant influence on the decision to stay. The conclusion of this study is the price and facilities it has. Influence on the decision to stay. With a price that is in accordance with the facilities obtained will make consumers decide to stay. Suggestions for Aloft Hotel Jakarta Wahid Hasyim to always offer competitive prices and well-maintained facilities.